2020
DOI: 10.1080/17513758.2020.1745306
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis dynamics: modelling the effects of treatment, education and vector control

Abstract: A deterministic model of onchocerciasis disease dynamics is considered in a community partitioned into compartments based on the disease status. Public health education is offered in the community during the implementation of mass treatment using ivermectin drugs. Also, larviciding and trapping strategies are implemented in the vector population with the aim of controlling population growth of black flies. We fit the model to the data to check the suitability of the model. Expressions are derived for the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the past, other authors have also reported an association between educational status and onchocerciasis infection [26]. Indeed, mathematical modeling studies reveal that education is a key intervention which contributes to controlling the dynamics of onchocerciasis transmission in endemic settings [33]. The annual biting rates along the Sanaga river observed in this study were a little lower compared to those in villages close to the Mbam River [5].…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…In the past, other authors have also reported an association between educational status and onchocerciasis infection [26]. Indeed, mathematical modeling studies reveal that education is a key intervention which contributes to controlling the dynamics of onchocerciasis transmission in endemic settings [33]. The annual biting rates along the Sanaga river observed in this study were a little lower compared to those in villages close to the Mbam River [5].…”
Section: Discussionmentioning
confidence: 43%
“…In the past, other authors have also reported an association between educational status and onchocerciasis infection [ 26 ]. Indeed, mathematical modeling studies reveal that education is a key intervention which contributes to controlling the dynamics of onchocerciasis transmission in endemic settings [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following [19,[24][25][26][27], the global stability of a system equilibrium point can be established by first expressing the system in a triangular form as follows:…”
Section: Global Stability Of Malaria-free Equilibriummentioning
confidence: 99%
“…Also, qualitative analysis with the impact of delays were investigated. Hassan and Shaban 35 formulated a onchocerciasis model and investigated the effect of delays, treatment, education, and vector control against the spread of onchocerciasis by fitting the model to data on the disease predominance in Cameroon, which suggest that the region needs steady application of these measures annually to minimize the spread of the disease.…”
Section: Introductionmentioning
confidence: 99%